Static and Dynamic Studies of Gasoline in View of its Octane Number and its Toxic Effect (JOURNAL OF ADVANCES IN CHEMISTRY, 2008)
Gasoline come primarily from petroleum cuts, it is the preferred liquid fuel in our lives. Two gasoline samples of octane numbers 91 and 95 from Saudi Arabia petrol stations were studied. This study was achieved at three different temperatures 20oC, 30oC and 50oC representing the change in temperatures of the different seasons of the year. Both the evaporated gases of light aromatic hydrocarbons (BTEX) of gasoline samples inside the tank were subjected to analyze qualitatively and quantitatively via capillary gas chromatography. The detailed hydrocarbon composition and the octane number of the studied gasoline samples were determined using detailed hydrocarbon analyzer. The idea of research is indicating the impact of light aromatic compounds in gasoline on the toxic effect of human and environment on the one hand, and on octane number of gasoline on the other hand. Although the value of octane number will be reduced but this will have a positive impact on the environment as a way to produce clean fuel.